Characterization of Colistin-Resistant Escherichia coli Isolated from Diseased Pigs in France - Delannoy, Sabine; Le Devendec, Laetitia; Jouy, Eric; Fach, Patrick; Drider, Djamel; Kempf, Isabelle (Frontiers in Microbiology, 2017)
We studied a collection of 79 colistin-resistant Escherichia coli strains isolated from diseased pigs in France between 2009 and 2013. We determined a number of phenotypic and genetic characters using broth microdilution to characterize their antimicrobial susceptibility. We performed pulse field gel electrophoresis (PFGE) to assess their genetic diversity and assign them to phylogroups. High-throughput real-time PCR micro-array was used to screen for a selection of genetic markers of virulence, and PCR and sequencing of the main recognized resistance genes allowed us to investigate the mechanisms of colistin resistance. Results showed that strains belonged to several phylogroups and most had a unique PFGE profile. More than 50% of the strains were also resistant to sulfonamides, trimethoprim, tetracycline, ampicillin or chloramphenicol. The mcr-1 gene was detected in 70 out of 79 strains and was transferred by conjugation in 33 of them, sometimes together with resistance to sulfonamides, trimethoprim, tetracycline, ampicillin, chloramphenicol, cefotaxime or gentamicin. Mutations in the amino-acid sequences of proteins MgrB, PhoP, PhoQ, PmrB, but not PmrA, were detected in strains with or without the mcr-1 gene. More than one-third of the strains harbored the F18, F4, astA, hlyA, estI, estII, elt, stx2e, iha, orfA, orfB, paa, terE, ecs1763 or ureD virulence markers. In conclusion, although most isolates had a unique PFGE profile, a few particular combinations of phylogenetic groups, virulence genes and mutations in the sequenced genes involved in colistin resistance were identified on a number of occasions, suggesting the persistence of certain strains over several years.